The influence of agility training on physiological and cognitive performance - Lennemann, L. M.; Sidrow, K. M.; Johnson, E. M.; Harrison, C. R.; Vojta, C. N.; Walker, T. B. (The Journal of Strength and Conditioning Research, 2013)
Agility training (AT) has recently been instituted in several military communities in hopes of improving combat performance and general fitness. The purpose of this study was to determine how substituting AT for traditional military physical training (PT) influences physical and cognitive performance. Forty-one subjects undergoing military technical training were divided randomly into 2 groups for 6 weeks of training. One group participated in standard military PT consisting of calisthenics and running. A second group duplicated the amount of exercise of the first group but used AT as their primary mode of training. Before and after training, subjects completed a physical and cognitive battery of tests including VO2max, reaction time, Illinois Agility Test, body composition, visual vigilance, dichotic listening, and working memory tests. There were significant improvements within the AT group in VO2max, Illinois Agility Test, visual vigilance, and continuous memory. There was a significant increase in time-to-exhaustion for the traditional group. We conclude that AT is as effective or more effective as PT in enhancing physical fitness. Further, it is potentially more effective than PT in enhancing specific measures of physical and cognitive performance, such as physical agility, memory, and vigilance. Consequently, we suggest that AT be incorporated into existing military PT programs as a way to improve war-fighter performance. Further, it seems likely that the benefits of AT observed here occur in various other populations.